AUSTRALIAN EARLY RETIREMENT TAX BIASES PRIOR TO JULY 2007 AND THE LIKELY EFFECTS OF TAX REFORM ON RETIREMENT PLANS - Felmingham, B; Jackson, N; Walter, M; Yan, Y.H (My University, 2008)
The demographic prognosis for the twenty-first century is that all national populations will age structurally and most in the developed world will ultimately decline in size. Australia's structural ageing is less pronounced than that in many other countries, but it will nevertheless experience reduced population growth a decade hence. One often stated concern is that the social security systems of nations like Australia will not be sustainable in their present form because the next generation will not be able to raise sufficient taxes to support a burgeoning pension bill. These intergenerational financial pressures are compounded by another trend, namely, that over the past fifteen years employees have been leaving the workforce at ages well below the now-defunct‘official’ retirement age, 65 years. In Australia and other nations this decline in labour force participation has been partly explained by generous social security provisions, but also by redundancy- and retrenchment-driven ‘structural retirement’ (Jackson, Walter, Felmingham and Spinaze, 2006).
Keywords: Intergenerational Transfer -- Welfare reliance; Employment -- Exit from employment (Retirement/Redundancy); Benefits and Payments; Ageing; Labour market; Intergenerational transfer; Benefits and Payments; Employment; Intergenerational Transfer; Exit from employment (Retirement/Redundancy); Welfare reliance; Employment and unemployment; Intergenerational transfer; Ageing